Valoración de las especies Ilex guayusa (GUAYUSA) y Plukenetia volubilis L. (SACHA INCHI), como una materia prima cosmética antioxidante. - Silva Escobar, Mishell Estefanía (2018)
The objective of this research work was to evaluate the antioxidant capacity of two species from the Ecuadorian Amazon, Ilex guayusa Loes. (Guayusa) and Plukenetia volubilis Linneo. (Sacha Inchi). It was proceeded with the development of three formulations in which the concentrations of the fluid extract of guayusa to 50% varied at 1.0%, 2.5% and 5.0% and a single concentration of 4.0% sacha inchi oil, of which the formulation with the best properties for the evaluation of cosmetic efficacy was selected, from quality control tests, preliminary stability, irritation and from the capture method of the DPPH radical (2.2 diphenyl-1-picryl hydrazyl), obtaining favorable results in all the formulations, however, the composite at 5.0% obtained better absorbance values, which indicated a good antioxidant activity for the extract immersed in the cosmetic formulation. The cosmetic efficacy study consisted of an in vivo panel of 12 women aged 30 to 45 years, same them that followed the application instructions of the cream in three sections of the face during the nights, in a lapse of 3 months, time in which monthly measurements were made with the help of the MPA 580 cutometer to evaluate the skin's firmness and elasticity, and in this way it was determined statistically the change that was experienced during the application period, same that indicated improvement for the criterion of viscoelasticity and criteria related to the relaxation of the skin.